Performance Evaluation of the Fire and Rescue Service in Handling Fire Problems in Ambon City - Reynold Nikijuluw; Dominggus Marsel Ibaigajir (Asosiasi Ilmuwan Administrasi Negara (AsIAN), 2025)
This study addresses a significant gap in decentralized emergency service governance by critically examining the institutional, operational, and jurisdictional dimensions of fire service performance in Ambon City. Existing studies predominantly focus on response time and infrastructural adequacy, offering limited analytical engagement with governance complexity and boundary-related challenges. Accordingly, this research investigates not only operational compliance but also broader structural factors that influence performance outcomes. Employing a qualitative case study approach, the study draws on in-depth interviews with fire and rescue officers, fire victims, and eyewitnesses, and on the analysis of institutional documents and Standard Operating Procedures (SOPs). Data were analyzed thematically to identify patterns in compliance, professional conduct, and inter-organizational coordination. The findings demonstrate that overall performance is institutionally robust, with officers generally adhering to the 15-minute response standard and established operational protocols. Nevertheless, procedural deviations persist in high-pressure situations, indicating constraints related to supervision, training, and resource allocation. Importantly, the study reveals recurring cross-jurisdictional responses to incidents in Central Maluku Regency, generating administrative ambiguity and ethical tension. By situating performance evaluation within a multi-level governance framework, this research advances a more comprehensive analytical model that integrates operational effectiveness with intergovernmental coordination, thereby contributing conceptual novelty to the study of local public service performance.